Population dynamics of Petrochirus diogenes (Crustacea, Anomura, Diogenidae) in the Ubatuba region, São Paulo, Brazil - Bertini, G.; Fransozo, A. (A A Balkema Publishers, 2000)
This work examines the population dynamics of Petrochirus diogenes in the Ubatuba region (São Paulo, Brazil), focusing on size frequency distribution, sex ratio, and reproductive and recruitment period. Collections were made with two double-rig nets in the years 1993-1996. The 799 individuals obtained were separated into 14 size classes based on the length of the cephalothoracic shield. The shield size varied from 5.4 to 40.0 mm in males and from 5.7 to 32.1 mm in females. The size frequency distribution was unimodal for both sexes. Only small oscillations occurred in the sex ratio until the seventh size class, followed by preponderance of males. This suggests a standard pattern for the sex ratio in P. diogenes. As males were found in the largest size classes, they present a clear sexual dimorphism. This characteristic can be considered as a selective advantage, mainly during the mating processes and in the agonistic behavior. Ovigerous females were recorded in the spring and summer, indicating seasonal reproduction.